2008
DOI: 10.1002/jcp.21463
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate increases superoxide production through mitochondrial electron transport chain and NADPH oxidase activity in skeletal muscle cells

Abstract: The effect of unbound palmitic acid (PA) at plasma physiological concentration range on reactive oxygen species (ROS) production by cultured rat skeletal muscle cells was investigated. The participation of the main sites of ROS production was also examined. Production of ROS was evaluated by cytochrome c reduction and dihydroethidium oxidation assays. PA increased ROS production after 1 h incubation. A xanthine oxidase inhibitor did not change PA-induced ROS production. However, the treatment with a mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 57 publications
5
99
2
6
Order By: Relevance
“…Similar results were observed by our previous studies (Lambertucci et al 2008) using primary cultures of skeletal muscle cells treated with palmitic acid. Rossary et al (2007) also observed an increased ROS production using fibroblasts treated with 15 μM of DHA for 4 h (even using a shorter fatty acid concentration and incubation time).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were observed by our previous studies (Lambertucci et al 2008) using primary cultures of skeletal muscle cells treated with palmitic acid. Rossary et al (2007) also observed an increased ROS production using fibroblasts treated with 15 μM of DHA for 4 h (even using a shorter fatty acid concentration and incubation time).…”
Section: Discussionsupporting
confidence: 92%
“…Fluorescent microscopy was used to measure fluorescent signal which was quantified using ImageJ 1.46r (Wayne Rasband, NIH, USA) using two photos per well selected at random. Palmitic acid at 100 μM was used as positive control for superoxide production as shown in previous studies (Lambertucci et al 2008(Lambertucci et al , 2012.…”
Section: Evaluation Of Ros Productionmentioning
confidence: 99%
“…Although the cause of the increased oxidative stress in high-fat diet-induced obesity is not completely understood, one possible reason is the increased supply of free fatty acids to the cells from triglyceride. Incubation of the skeletal muscle with palmitate for 1 h induces superoxide production in the skeletal muscle (26), and high-fat meal for 5 days in lean humans increases mitochondria hydrogen peroxide production and reduces antioxidants capacity (27). Fat content in thigh muscle are negatively correlated with insulin sensitivity in obese type 2 diabetic patients (28), and diet restriction reduces triglyceride levels and oxidative stress in skeletal muscle, which is associated with improved insulin sensitivity in Goto-Kakizaki rats (29).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of FFA on ROS production has been examined in numerous cell types [50,51] . ER stress and ROS are proposed to be involved in cell death.…”
Section: Discussionmentioning
confidence: 99%